Strategies to Increase National Integration in the Era of Globalization - Fatia Muara Aini; Nazla Andini; Zulaikha Azzahra (Lembaga Studi Agama dan Masyarakat Aceh, 2025)
The era of globalization brings challenges to Indonesia's national integration, especially with the rapid development of technology and the rapid flow of information. Cultural, religious, and socioeconomic differences are increasingly complex and have the potential to cause conflicts that can hinder the unity of the nation. This research aims to analyze strategies in strengthening national integration in the midst of these challenges. The method used is a literature study by collecting and analyzing various reliable sources related to national integration. The results show that the main challenges in national integration include digital access gaps, cybersecurity threats, as well as global cultural influences that can erode local values. To overcome these challenges, strategies such as equitable digital access, increasing technological literacy, and strengthening national values through education and social media are needed. In addition, collaboration between the government, educational institutions, and the community is needed to build a collective awareness of the importance of unity in diversity. By utilizing technology positively and instilling the spirit of tolerance and togetherness, national integration can be strengthened to build a more harmonious, stable, and competitive nation in the era of globalization